2012
DOI: 10.1007/s12603-012-0042-z
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and vascular dementia

Abstract: Currently, the most convincing evidence as to the relationship between VaD and nutrition exists for micronutrients, particularly Vitamin E and C. Exploration of nutrition at the macronutrient level and additional long term prospective cohort studies are warranted to better understand the role of nutrition in VaD disease development and progression. At present, challenges in this research include limitations in sample size, which was commonly cited. Also, a variety of diagnostic criteria for VaD were employed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…The protective effect of fish intake against cerebral vascular disease risk (including stroke and VCI) is established [64,65]. Although, omega-3 fatty acids (docosahexaenoic acid and eicosapentaenoic acid) in fish have been largely implicated in the protection, other nutritional constituents of fish including vitamins D and B complex, essential amino acids and trace elements in fish (for example, taurine, arginine, selenium, calcium, magnesium, potassium, and iodine) may have potentially favorable effects on inflammation, endothelial function, vascular tone, neuronal functioning and cell death [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of fish intake against cerebral vascular disease risk (including stroke and VCI) is established [64,65]. Although, omega-3 fatty acids (docosahexaenoic acid and eicosapentaenoic acid) in fish have been largely implicated in the protection, other nutritional constituents of fish including vitamins D and B complex, essential amino acids and trace elements in fish (for example, taurine, arginine, selenium, calcium, magnesium, potassium, and iodine) may have potentially favorable effects on inflammation, endothelial function, vascular tone, neuronal functioning and cell death [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…A diet rich in saturated fat is associated with faster cognitive decline and increased risk of dementia [72,78]. On the contrary, fish consumption, rich in omega-3 polyunsaturated fatty acids has been shown as protective against cognitive decline [78].…”
Section: Cognitive Functionmentioning
confidence: 99%
“…This subsequently produces of S-adenosylmethionine (SAM), which plays a role in neurotransmitter synthesis and lipid metabolism [1]. Folate deficiency results in elevated levels of plasma homocysteine, which have been associated with cardiovascular disease [2], neurodegeneration [3], impaired cognitive function [4,5], the development of Alzheimer's disease (AD) [6][7][8], and vascular dementia [9][10][11]. However, the neurodegeneration link remains controversial, since other studies have shown no association [12][13][14].…”
Section: Introductionmentioning
confidence: 99%